THE RISE OF CRITICAL SOCIAL THOUGHT - Lengermann, Patricia; Niebrugge-Brantley, Jill (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this course is to introduce you to an important tradition in the history of ideas, the rise of critical social thought. Critical social thought is that system of thinking and ideas which allows individuals to study the social world as a human product which can be changed and improved by human effort. Critical thought as a tradition and a practice calls us both to understanding and to action. It is in some measure the source of our democracy, our liberty, and our sense of collective responsibility. The course is organized as a lecture/discussion focused on the essential elements of critical social thought: (1) the intelligence–and courage–to "see through" the taken-forgranted arrangements of the everyday world to the processes that produce and reproduce them; (2) the critique of injustice in that everyday world which requires taking the point of view of less powerful groups, and (3) the quest for strategies to bring about change toward a more just social world. We explore this tradition of critical social thought by focusing on some of the major ideas of thinkers who helped create sociology in the nineteenth and early twentieth centuries.